You Support Diversity, But Are You Ethical? Examining the Interactive Effects of Diversity and Ethical Climate Perceptions on Turnover Intentions - Stewart, Robert W. (2011)
Efforts to identify antecedents of employee turnover are likely to offer value to organizations through money saved on recruitment and new-hire training. The authors utilized the stakeholder perspective to corporate social responsibility to examine the effects of a perceived climate for ethics on the relationship between diversity climate and voluntary turnover intentions. Specifically, they examined how ethics climate (employees’ perceptions that their organization values and enforces ethically correct behavior) affected the diversity climate–turnover intentions relationship. Results indicated that ethics climate moderated the diversity climate–turnover intentions relationship. Turnover intentions were lowest among workers perceiving both a pro-diversity and highly ethical climate. These results reinforce the need to communicate both diversity values and ethical standards to employees.
Keywords: Corporate Social Responsibility; Turnover intentions; Ethical Climate; diversity climate